Additive-treated corn and forage sorghum silages for growing cattle - Bolsen, K.K.; Laytimi, A.; Hart, R.A.; Niroomand, F.; Hoover, J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Whole-plant corn silages were treated with Ecosyl® or Foraform® in one trial and Biomate® or Biomate + Cold-flo® in the second trial. In both trials, the silages were well preserved, but all were highly unstable in air during the first 3 to 4 weeks of the feed-out period. Foraform-treated silage was 2 to 6 degrees F cooler than its control, but Cold-flo-treated silage was 2 to 8 degrees F warmer during the first 10 days post-filling. Laboratory silo results showed that both control silages fermented extremely fast; however, inoculated silages had slightly lower pH and higher lactic acid values through the first 4 to 7 days postfilling. Foraform lowered the initial pH of the ensiled material, restricted subsequent fermentation, and produced a silage with about one-half the acid content compared to its control. Cold-flo raised the initial pH and delayed the start of fermentation, but resulted in a silage with greater acid content and an increased dry matter loss. Though not significant, calves fed Ecosyl, Foraform, and Biomate silages had about 6 percent better feed conversion than those fed control silages and gain per ton of crop ensiled was also higher for the three treated silages. Cold-flo-treated silage produced 3.5 lb less gain per ton of crop ensiled than its control. Whole-plant forage sorghums were treated with TriLac® in one trial and Silagest® in the second trial. Inoculated silages had slightly lower ensiling temperatures than controls. All silages fermented rapidly, but both inoculants increased ensiling efficiency as indicated by higher lactic to acetic acid ratios (in laboratory silos) and decreased dry matter losses (in farm-scale silos). Calves fed Silagest silage outperformed those fed control silages, and both inoculants increased gain per ton of crop ensiled over control silages.
Keywords: Beef; Corn; Sorghum; Growing cattle